Mathematics Resiliency in the New Normal: A Theory Development - Callaman, Roar A. (S&Co Publishing, 2023)
This paper aimed to generate a theory that answers the question, “How do students cope with the challenges in learning mathematics in the normal? This study made used of the deductive axiomatic approach in theory generation following the steps prescribed by Padua (2012). Four axioms were formulated: (1) Students employ time management in studying math; (2) Students uses compensation strategies in overcoming challenges; (3) Students’ resourcefulness leads them to learn mathematics; and (4) Students asked help from teachers and peers in understanding mathematical concepts. Two propositions were derived from these axioms: students’ cope with the challenges in learning mathematics by (1) direct coping strategies support students’ resiliency in learning mathematics and (2) Indirect coping strategies indirectly provide support for coping strategies through planning, socializing with others and increasing empathy. From these propositions, the Students’ Mathematics Resiliency Based Theory is formulated: The Students’ Mathematics Resiliency Theory states that resiliency in learning mathematics is affected by both direct and indirect coping strategies. Direct coping strategies include compensation strategies, while indirect strategies include social, time management, and resourcefulness.